Pengaruh Pengalaman Audit, Skeptisisme Profesional, Dan Tekanan Waktu Terhadap Kemampuan Auditor Mendeteksi Fraud - Stefani Tanus; Anwar (Insan Cita Bongaya Research Journal, 2024)
This research was conducted to determine the influence of audit experience, professional skepticism, and time pressure on auditor’s ability to detect fraud at the regional inspectorate of south sulawesi province. The data source in this research is primary data in the form of answers to a questionnaire to the auditor of the regional inspectorate of south sulawesi province. The sampling method in thisr esearch used the saturated sample method and from this method 41 samples met the criteria. The data analysis technique in this research uses multiple linear regression analysis, where there search results show that the audit experience, professional skepticism, and time pressure have a significant positive effect on the auditor’s ability to detect fraud